Measurements of properties of the Higgs boson decaying into the four-lepton final state in pp collisions at √s=13 TeV - CMS, The CMS collaboration; Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Ambrogi, Federico; Md. Ali, Mohd. Adli (Springer Verlag, 2017)
Properties of the Higgs boson are measured in the H → ZZ → 4` (` = e, µ) decay channel. A data sample of proton-proton collisions at √ s = 13 TeV, collected with the CMS detector at the LHC and corresponding to an integrated luminosity of 35.9 fb−1 is used. The signal strength modifier µ, defined as the ratio of the observed Higgs boson rate in the H → ZZ → 4` decay channel to the standard model expectation, is measured to be µ = 1.05+0.19 −0.17 at mH = 125.09 GeV, the combined ATLAS and CMS measurement of the Higgs boson mass. The signal strength modifiers for the individual Higgs boson production modes are also measured. The cross section in the fiducial phase space defined by the requirements on lepton kinematics and event topology is measured to be 2.92 +0.48 −0.44(stat) +0.28 −0.24(syst) fb, which is compatible with the standard model prediction of 2.76±0.14 fb. Differential cross sections are reported as a function of the transverse momentum of the Higgs boson, the number of associated jets, and the transverse momentum of the leading associated jet. The Higgs boson mass is measured to be mH = 125.26 ± 0.21 GeV and the width is constrained using the on-shell invariant mass distribution to be ΓH < 1.10 GeV, at 95% confidence level.